Difference in authenticity perception of old towns among China's various cultural regions. Issue 2 (18th October 2021) - Wu, Ying; Wang, Fang; Mao, Wen; Xu, Shuangyu; Xu, Shuangyu; Tang, Jintong
Abstract : Purpose: Regarding research on authenticity perception, this paper aims to pose the following questions: In different cultural regions, what are the different authenticity elements of old towns from a tourist perspective? What is the difference in authenticity perception in different cultural regions? How does the authenticity perception of old towns change in the tourismification process? Design/methodology/approach: Combining eight cultural regions in China, this study focuses on 155 old towns to discuss the differences between authenticity perception of various old towns in different cultural regions and how the interactions between tourists and local places influence the perception of authenticity, with 11, 387 user-generated photographs applied to interpret authenticity perception. Findings: The study shows that the authenticity perceived by tourists varies greatly between farming and pastoral cultural regions; after authenticity loss, old towns with a long history of tourismification regain authenticity in tourists' perception. Originality/value: The findings could serve as a reference for tourism development and authenticity protection of old towns. Furthermore, the study explores a creative research method and theoretical framework for regional authenticity studies, which is significant in a global context. In the process of globalization, the implications of this study, including differences in authenticity perception within various cultural regions, will also be significant globally.